Synthesis, characterization, and antibacterial activity of copper oxide nanosheets - Shahmiri, Mahdi (2013)
The investigation on nanoparticles, which includes fabrication and characterization of the structural, physical, and chemical properties and their functions in various field of technology, is a fundamental cornerstone of nanotechnology and nanoscience. The applications of nanoparticles are known in many fields, such as catalysis, coating, semiconductors, and electronics. Among all practical matters that are produced at the nanometer scale, metal oxides are mainly attractive candidates from a technological and scientific point of view. Amongst all metal oxide nanoparticles, copper oxide (CuO) has gained the most interest because of its wide applications. During the past decades different methods have been proposed to synthesis CuO nanoparticles. Some of these methods have limitations due to requirements for high temperature, expensive instruments and special catalysis. In this study fabrication of CuO nanosheets in polyvinylpyrrolidone (PVP) by the quick precipitation method was investigated. The main advantages of this method compared to other methods are environmentally friendly, cost-effectiveness, producing pure materials and simplicity of operation. Synthesis parameters include pH, concentration of stabilizer, and molar ratio of Cu2+ and OH- were varied and their influences on the properties of CuO were investigated. Copper nitrate trihydrate Cu(NO3)2.3H2O, polyvinylpyrrolidone (PVP) and sodium hydroxide (NaOH) were utilized as copper precursor, stabilizer and reducing agent, respectively. As evidenced by XRD analysis, all the products synthesized at pH 10 and 12 were CuO with monoclinic structure and all the products obtained under acidic pH were copper hydroxyl nitrate (Cu2(OH)3NO3). Electron microscopy analysis illustrated that nanocrystals have a sheet-like geometry. By careful observation of electron microscopy revealed that oriented attachment mechanism was responsible for formation nanosheets from nanosized subunits. EDAX clearly confirmed the existence of Cu and O with an atomic ratio of 1:1 in all samples synthesized at pH 10 and 12. Diffuse reflectance spectroscopy studies revealed that the band gap of CuO nanosheets was found to be size-dependant. FT-IR spectroscopy was applied in this work to study the bonding at the surface of the synthesized CuO nanosheets. The result of FT-IR indicated that C=O in PVP Coordinated with CuO nanosheets and formed a protection layer. Investigation of effect of molar ratios of Cu2+ and OH- on CuO indicated that when the molar ratio of Cu2+ and OH- is 1:1, the final product is not pure. The pure monoclinic CuO were formed at the molar ratio of 1:3 and 1:4. From electron microscopy studies, sheet-like CuO at the molar ratio of 1:3 and 1:4 and ellipsoid-shape at a molar ratio of 1:1 were formed. The as synthesized CuO nanosheets were examined for antibacterial activity against four human pathogens, including two Gram-positive (Staphylococcus. areas and Bacillus. subtilis) and two Gram-negative (Salmonella and Klebsiella pneumonia). The antibacterial activity of CuO nanosheets was found to be size dependent. The zone of inhibition increased as particle size decreased. The main observation was that CuO nanosheets indicated greater antimicrobial activity against Gram-positive bacteria. The inhibition zone for all microorganisms reached the maximum using CuO nanosheets fabricated in PVP 5% wt at pH 10.